1995
DOI: 10.1002/xrs.1300240403
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐dispersive measurement and comparison of different spectra from diffraction x‐ray tubes

Abstract: Direct measurement of the spectral distribution emitted by an x‐ray tube with a solid‐state detector is described. Spectral distributions of various x‐ray tubes differing in anode material were measured and compared. Numerical values and relevant data for Cu, Mo and W x‐ray tubes are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Undoubtedly Ebel's model 2 gives lower mean absolute differences compared with Görgl et al's model. 8 From the values in Table 2, it can be observed that the mean absolute differences range from 1 to 44% depending on the secondary target and the tube spectral distribution model used. However, these differences decrease with increase in operational voltage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Undoubtedly Ebel's model 2 gives lower mean absolute differences compared with Görgl et al's model. 8 From the values in Table 2, it can be observed that the mean absolute differences range from 1 to 44% depending on the secondary target and the tube spectral distribution model used. However, these differences decrease with increase in operational voltage.…”
Section: Resultsmentioning
confidence: 99%
“…19 For these calculations, two models of tube spectral distributions were used, as described elsewhere. 2,8 Absorptions due to air paths and Kapton absorbers were also taken into account. The experimental and calculated K˛fluorescence intensities were next normalized to their corresponding values at 40 kV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A first evaluation of a measured Mo spectrum for presentation in photons s 1 sr 1 mA 1 keV 1 versus photon energy in keV is described. Further investigations by Görgl et al 47,48 deal with measured responses and the influence of different tube voltages and target materials on the measured spectra. Finally, Aiginger et al 49 measured spectral responses from Cr, Mo, Rh and W tubes and compared their results with measured spectra from Gilfrich 50 and with computed spectra from Schossmann's approach.…”
Section: Comparison To Other X-ray Tube Spectramentioning
confidence: 99%
“…Analytical descriptions of x-ray tube spectra have been widely reported in the literature. Some of them are the result of direct measurement of specific x-ray tubes, as described by Görgl and co-workers, 16,17 while others are considered as semi-empirical, like the models of Ebel and co-workers, 18 -21 and Pella et al 22,23 In order to investigate the extent to which the theoretical description of the secondary x-ray beam after a fluorescer target depends on the choice of the initial tube spectral distribution, we adopted in our calculations the use of all the three models mentioned above.…”
Section: Introductionmentioning
confidence: 99%